UJI KEPRAKTISAN ALAT EKSPERIMEN KINEMATIKA GERAK LURUS SEBAGAI MEDIA PEMBELAJARAN IPA FISIKA SMP - Mangamar, Sutan; Fakhruddin, Fakhruddin; Sudrajad, Hendar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: this study aims to test the practicality of the device straight motion kinematics experiment as a medium of learning science in junior high school, resulting in a practical device is used as the medium of instruction. The object of this research is a straight motion kinematics experiment consisting of experimental tools and books guides experiments. data collection is done by giving the now practicality to teachers and students, which consists of 3 science teachers and 20 Junior High School students. The data analyzed are descriptive to determine the value of the experiment device of practicality. The results of the analysis of the data obtained are, the assessment of practicality of experimental instruments of straight motion kinematics and experiment manuals are in the high and very high categories. Based on the analysis of the data it can be concluded that the device straight motion kinematics experiment consisting of tools and guidebooks wants a practical and feasible has been used as a medium of learning science of junior high school.Key Words: Practicality, straight motion kinematics, device experiment